Microbial Community and Its Association With Physicochemical Factors During Compost Bedding for Dairy Cows - Sun, Likun; Han, Xiangmin; Li, Jianshu; Zhao, Zhidong; Liu, Yuzhen; Xi, Qiming; Guo, Xinyu; Gun, Shuangbao (Frontiers in Microbiology, 2020)
Overproduction of livestock manure can cause significant environmental challenges. Compost bedding (CB) is considered an effective approach for recycling the agricultural byproducts and improving the welfare of dairy cattle. During the CB preparing, the composition of microbial communities is usually altered; however, the patterns and drivers of CB microbial communities remains to be investigated. The current study aimed to explore the dynamics of bacterial and fungal communities during the various padded stages, using high throughput sequencing technology and qPCR. The relationships across physicochemical parameters, microbial community composition, and abundance were also evaluated. Sequencing results revealed that Proteobacteria, Bacteroidetes, Actinobacteria, and Firmicutes of bacteria, and Ascomycota of fungi as the major phyla found in CB. qPCR results showed a significant increase in the number of bacterial genome copies from 1.20 × 107 to 3.35 × 107 copies/gram of dry soil, while the number of fungal genome copies significantly increased from 8.43 × 104 to 7.02 × 106 copies/gram of dry soil. Linear discriminant analysis effect size (LEfSe) showed that Actinobacteria was the primary indicator in raw materials while the phylum Bacteroidetes was in the other padded stages. Dothideomycetes was significantly enriched in the initial stage of fungi, whereas Sordariomycetes, including a pathogen Scedosporium prolificans, was the major indicator in CB after 9 days of padding. Mantel test showed that pH significantly influenced bacterial community composition while temperature and total organic carbon (TOC) had a significant effect on fungal community structure. Redundancy analysis indicated that TOC, temperature, and water content had a significant effect on bacterial abundance while total nitrogen, water content, and pH significantly affected fungal abundance. Our finding contributed to the understanding of microbial community succession in CB across different padded stages, and suggests CB management by changing the bedding material every 7 days.